Selecting accurate post-elimination monitoring tools to prevent reemergence of urogenital schistosomiasis in Morocco: a pilot study - Abdelaali Balahbib; Fatima Amarir; Paul L.A.M. Corstjens; Claudia J. de Dood; Govert J. van Dam; Amina Hajli; Meryem Belhaddad; Bouchra El Mansouri; Abderrahim Sadak; Mohamed Rhajaoui; El Bachir Adlaoui (BMC, 2017)
Abstract Background After alleged stop of transmission of schistosomiasis and further down the line in post elimination settings, sensitive tools are required to monitor infection status to prevent potential re-emergence. In Rahala, where transmission cycle of Schistosoma haematobium is interrupted since 2004 but where 30% of snails are still infected by S. bovis, potential human S. bovis infection can't be excluded. As methods based on egg-counts do not provide the required sensitivity, antibody or antigen assays are envisaged as the most appropriate tools for this type of monitoring. Methods In this pilot study, the performances of three assays were compared: two commercially available antibody tests (ELISA and haemagglutination format) indicating exposure, and an antigen test (lateral flow strip format) demonstrating active infection. All 37 recruited study participants resided in Rahala (Akka, province Tata, Morocco). Participants had been diagnosed and cured from schistosomiasis in the period between 1983 and 2003. In 2015 these asymptomatic participants provided fresh clinical samples (blood and urine) for analysis with the aforementioned diagnostics tests. Results No eggs were identified in the urine of the 37 participants. The haemagglutination test indicated 6 antibody positives whereas the ELISA indicated 28 antibody positives, one indecisive and one false positive. ELISA and haemagglutination results matched for 18 individuals, amongst which 5 out of 6 haemagglutination positives. With the antigen test (performed on paired serum and urine samples), serum from two participants (cured 21 and 32 years ago) indicated the presence of low levels of the highly specific Schistosoma circulating anodic antigen (CAA), demonstrating low worm level infections (less than 5 pg/ml corresponding to probably single worm pair). One tested also CAA positive with urine. ELISA indicated the presence of human anti-Schistosoma antibodies in these two CAA positive cases, haemagglutination results were negative. Conclusions To prevent reemergence of schistosomiasis in Morocco current monitoring programs require specific protocols that include testing of antibody positives for active infection by the UCP-LF CAA test, the appropriate diagnostic tool to identify Schistosoma low grade infections in travelers, immigrants and assumed cured cases. The test is genus specific will also identify infections related to S. bovis.